Comprehensive Biochemical, Physiological, and Transcriptomic Analyses Provide Insights Into Floral Bud Dormancy in Rhododendron delavayi Franch - Zhang, Lu; Song, Jie; Peng, Lvchun; Xie, Weijia; Li, Shifeng; Wang, Jihua (Frontiers in Genetics, 2022)
The ornamental woody flower Rhododendron delavayi Franch. was examined for its low temperature-induced floral bud-dormancy (late October-end December) aspect due to a scarcity of relevant data. The research was conducted to reveal the interplay among endogenous hormones and bud-dormancy phases viz: pre-dormancy, para-dormancy, endo-dormancy, eco-dormancy, and dormancy-release, via transcriptome data profiling along with co-expression network analyses. The biochemical and physiological assays revealed the significance of the abundance of phytohormones (abscisic acid, auxin, zeatin and gibberellins), carbohydrates metabolism, oxidative species, and proteins (soluble proteins, proline and malondialdehyde) in the regulatory mechanism of floral bud dormancy. The transcriptome sequencing generated 65,531 transcripts, out of which 504, 514, 307 and 240 expressed transcripts were mapped uniquely to pre-, para-, endo-, and eco- phases of dormancy, showing their roles in the stimulation of dormancy. The transcripts related to LEA29, PGM, SAUR family, RPL9e, ATRX, FLOWERING LOCUS T, SERK1, ABFs, ASR2, and GID1 were identified as potential structural genes involved in floral bud-dormancy. The transcription factors, including Zinc fingers, CAD, MADS-box family, MYB, and MYC2, revealed their potential regulatory roles concerning floral bud-dormancy. The gene co-expression analysis highlighted important hub genes involved in cold stress adaptations encoding proteins viz; SERPIN, HMA, PMEI, LEA_2, TRX, PSBT, and AMAT. We exposed the connection among low temperature-induced dormancy in floral buds, differentially expressed genes, and hub-genes via strict screening steps to escalate the confidence in selected genes for being truly putative in the pathways regulating bud dormancy mechanism. The identified candidate genes may prove worthy for further in-depth studies on molecular mechanisms involved in floral bud-dormancy of Rhododendron species